Interaction of a Preventative Fungicide Treatment and Root Rot Pathogen on Ambrosia Beetle Attacks during a Simulated Flood Event - Karla Addesso; Fulya Baysal-Gurel; Jason Oliver; Christopher Ranger; Paul O’Neal (Insects, 2018)
Flooding can increase tree susceptibility to root rot pathogens as well as attacks by ambrosia beetles attracted to stress-induced ethanol emissions. The objective of this study was to investigate the interaction of a preventative fungicide treatment and root infection with Phytophthora cinnamomi on ambrosia beetle attacks in flood stressed trees. A fungicide (Pageant® Intrinsic®) was evaluated in two flood trials using Eastern redbud and tulip poplar trees with treatments including the fungicide with or without pathogen or no fungicide with or without pathogen. Fungicide treated trees had fewer ambrosia beetle attacks, particularly in trees without P. cinnamomi co-infection. In a follow-up experiment, ethanol content was evaluated in flooded redbuds to determine if the fungicide treatment reduced stress-induced compounds. All flood stressed trees began producing ethanol within 24 h post flooding, regardless of fungicide treatment or P. cinnamomi infection. We conclude that pre-treatments of a fungicide can provide protection from ambrosia beetle attacks during an extreme flood event, but that protection is reduced if a root rot pathogen is also present. Additionally, rejection of fungicide treated trees was not related to the absence of ethanol, as the fungicide-treated plants released ethanol in quantities similar to non-treated trees.